Retinal vascular changes and arterial stiffness during 8-month isolation and confinement: the SIRIUS-21 space analog mission - Elmoselhi, Adel B.; Shankhwar, Vishwajeet; Qaisar, Rizwan; Hamoudi, Rifat; Brix, Bianca; Salon, Adam; Goswami, Nandu (Frontiers in Physiology, 2024)
Introduction: Isolation and confinement are significant stressors during space travel that can impact crewmembers' physical and mental health. Space travel has been shown to accelerate vascular aging and increase the risk of cardiovascular and cerebrovascular disorders. However, the effect of prolonged isolation and confinement on microvascular function has not yet been thoroughly investigated.Methods: Retinal vascular imaging was conducted on four crewmembers during-and post-8month SIRIUS-21 space analog mission. Central retinal arteriolar equivalent (CRAE), central retinal venular equivalent (CRVE), and arteriovenous ratio (AVR) were measured. Pulse wave velocity (PWV), an indicator of arterial stiffness, was also measured.Results: Data from 4 participants was analyzed. These participants had a mean age of 34.75 ± 5.44 years, height of 170.00 ± 2.00 cm, weight of 74.50 ± 12.53 kg, and average BMI of 25.47 ± 3.94 kg/m². During-and post-isolation, average CRVE showed an upward trend (Pearson's r 0.784, Rsquare 0.62), suggesting a dilation of retinal venules, while AVR showed a downward trend (Pearson's r -0.238, R-square 0.057), which is suggestive of a higher risk of cardiovascular and cerebrovascular dysfunctions. But neither of these trends were statistically significant.Additionally, the average PWV showed an upward trend during-and after-isolation across all crew members.Isolation and confinement appear to contribute towards retinal vascular damage and arterial stiffness. This cautiously suggests an increased risk of cardiovascular and cerebrovascular disorders due to the contribution of the isolation in space flight. Further studies are needed to confirm and expand on these results as we prepare for future manned missions to the Moon and Mars.